USE OF MARKET INFORMATION AND IMPLEMENTATION OF AUTOMATIC ANALYSIS SYSTEMS IN SMALL BUSINESS ENTITIES (Marketing Journal, 2026)
This article explores the potential for implementing real -time analytics systems based on machine learning (ML) technologies to enhance the use of market information by small and medium -sized enterprises (SMEs). The research methodology includes a systemat ic literature review, comparative evaluation of algorithms, and analysis of the current state of SMEs in Uzbekistan. The findings suggest that ML technologies can improve SME competitiveness, optimize data -driven decision -making processes, and reduce opera tional costs. Practical mechanisms for implementing real -time market analysis systems for SMEs in the context of Uzbekistan are proposed. № 1 -SON YANVA R, 202 6-YIL 107
Keywords: machine learning; small business; real -time analytics; artificial intelligence; market information; digital transformation